2016
DOI: 10.1186/s12870-016-0938-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcriptional response to heat stress in Rhazya stricta

Abstract: BackgroundClimate change is predicted to be a serious threat to agriculture due to the need for crops to be able to tolerate increased heat stress. Desert plants have already adapted to high levels of heat stress so they make excellent systems for identifying genes involved in thermotolerance. Rhazya stricta is an evergreen shrub that is native to extremely hot regions across Western and South Asia, making it an excellent system for examining plant responses to heat stress. Transcriptomes of apical and mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 104 publications
3
27
0
Order By: Relevance
“…Our prior analysis of R . stricta transcriptomes under heat stress supports the data generated for genes encoding chaperones and those encoding protein transparent testa 12 (tt12) under salt stress, where these genes were also highly upregulated under heat stress [29]. This indicates that mechanisms of tolerance against heat and salt stresses in this wild plant species rely partially on the response of the genes preventing degradation or protecting protein folding under either stress.…”
Section: Resultssupporting
confidence: 72%
“…Our prior analysis of R . stricta transcriptomes under heat stress supports the data generated for genes encoding chaperones and those encoding protein transparent testa 12 (tt12) under salt stress, where these genes were also highly upregulated under heat stress [29]. This indicates that mechanisms of tolerance against heat and salt stresses in this wild plant species rely partially on the response of the genes preventing degradation or protecting protein folding under either stress.…”
Section: Resultssupporting
confidence: 72%
“…TFs are important in signaling pathways to alter plant functions that would adversely affect the plant under abiotic stress conditions 62 , and therefore are also indicators of stress response and often associated with HSP up-regulation. For this study we focused on TFs that have been recognised in heat stress response through DEGs in previous studies 17, [63][64][65] and had DEGs (>2-fold) under heat stress conditions for these ecotypes. TFs can be up-regulated or down-regulated under abiotic stress conditions in plants 10,42 and in this study both occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Several transporters responsible for water, ion, and metabolite transport were heat stress-increased, such as aquaporins, vacuolar H + -ATPase, H + -pyrophosphatase, and ATP-binding cassette (ABC) transporters (Supplementary Table S1 ). Aquaporins are known to be associated with heat stress ( Christou et al, 2014 ; Obaid et al, 2016 ). The vacuolar H + -ATPase and H + -pyrophosphatase are required for membrane potential, pH homeostasis, and secondary solute transport during adaptation to a variety of abiotic stresses ( Gaxiola et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…To counteract the detrimental effects of heat stress, plants have employed multiple stress-tolerant strategies by altering the gene expression, protein synthesis, and post-translational modification, which contribute to the reestablishment of cellular homeostasis for plant survival under high temperature ( Bokszczanin et al, 2013 ). Recent transcriptomic studies have identified a large number of heat stress-responsive genes closely related with heat tolerance in various plant species including Arabidopsis thaliana ( Higashi et al, 2015 ), rice ( Oryza sativa ) ( Zhang et al, 2013 ), maize ( Zea mays ) ( Li et al, 2017 ), spinach ( Spinacia oleracea ) ( Yan et al, 2016 ), potato ( Solanum tuberosum ) ( Hancock et al, 2014 ), grape ( Vitis vinifera ) ( Rocheta et al, 2014 ; Jiang et al, 2017 ), perennial ryegrass ( Lolium perenne ) ( Wang K. et al, 2017 ), Rhazya stricta ( Obaid et al, 2016 ), carnation ( Dianthus caryophyllus ) ( Wan et al, 2015 ), and Saccharina japonica ( Liu F. et al, 2014 ). These heat stress-responsive genes were involved in various biological processes such as transcription regulation, alternative splicing, antioxidant defense, photosynthesis, protein homeostasis, as well as metabolisms of carbohydrates, lipids, amino acids, and secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%